Genetic analysis of rabies and rabies-related viruses in southern Africa, with emphasis on virus isolates associated with atypical infection patterns - Nel, Louis Hendrik (University of Pretoria, 2013)
Dissertation (MSc (Agric) Microbiology)--University of Pretoria, 1997.